Evaluating the Implementation of a Mental Health App for Overseas Filipino Workers in Macao China: A Mixed-Methods Study of Stakeholders’ Perspectives - Liem, Andrian; Pakingan, Karmia A.; Garabiles, Melissa R.; Sit, Hao Fong; Burchert, Sebastian; Lam, Agnes I. F.; Hall, Brian J. (Frontiers in Psychiatry, 2022)
Background: Overseas Filipino workers (OFWs) is one of the largest communities of international migrant workers. They face systemic barriers to fulfilling their health needs. The COVID-19 pandemic worsened this condition and provided a context to evaluate the utility of a digital mental health intervention delivered within a stepped-care model to address OFW mental health. Using an implementation science framework, this study aimed to evaluate stakeholders’ perspectives on the implementation of Kumusta Kabayan, a mobile phone-based mental health app, for OFWs in Macao. Methods: A mixed-methods convergent design was used by conducting two parallel steps, including quantitative and qualitative measures. The quantitative data was collected from Filipino team members and local non-governmental organization (NGO) staff members (N = 12). The qualitative data were gathered from interviews with OFWs in Macao who used the app (N = 25; 80% females, 76% domestic workers). Results: From the online survey, the staff members of the local partner NGO and the Filipino team members strongly perceived that their organization could adapt Kumusta Kabayan to their program and generally evaluated that Kumusta Kabayan achieved its goal and was received well by OFWs. In the interviews, the OFW app users shared their experiences in using Kumusta Kabayan, which was thematically organized into six aspects of the participants’ experience:1) promotional channel and expectation; 2) when to use the app and in what language; 3) lessons learnt; 4) memorable aspects; 5) key facilitators and barriers; and 6) suggestions. Conclusion: Kumusta Kabayan was well accepted and shows potential to be integrated into the existing support services for OFWs in Macao. This app has the promise of being scaled-up for OFWs in other countries by collaborating with local and overseas stakeholders. Lessons learnt from this evaluation could also be implemented in wider digital mental health services in different settings.